Traders' Understanding of Trade Zakat Accounting and Its Implementation in Kel. Balla Kec. Baraka Kab. Enrekang - Suarni, Agusdiwana; Sahrullah, Sahrullah; Arisaldi, Muh. (Jurnal Ar-Ribh, 2023)
This study aims to find out how merchants understand accounting for trade zakat and its implementation in Balla Village, Baraka District, Enrekang Regency. This type of research is a qualitative research method. The processed data is the result of interviews with 7 (seven people) traders in the balla family and UPZ 1 administrators (one person). This research resulted in the following findings: first, based on the results of research conducted by researchers that the understanding of traders in the Balla sub-district regarding trade zakat accounting is still lacking. Because most traders do not really understand the procedures for implementing trade zakat accounting, even though among the traders who have been interviewed by researchers there are only some who already understand the nishab and haul of trade zakat, and how much measure must be issued, but the calculation procedure is not correct. with the accounting standard for trade zakat accounting, namely 2.5% x (current assets - short term debt) Second: Implementation of trade zakat in the Balla sub-district, Baraka sub-district, Enrekang district regarding trade zakat accounting has been realized but not optimal because only a small number of traders have issued zakat trading results even though the calculation procedures they use are not correct. Due to the lack of information they get regarding trade zakat accounting, it is still lacking and most traders have not received information regarding trade zakat accounting, either from community shops or religious shops. Or institutions related to amil zakat bodies